The Risks Faced by Financing in Islamic Banks in Sudan: (A field study on a sample of Islamic banks in Sudan) - د.حمزهبشريجمةأحمدابكر (White Nile Journal for Studies and Research, 2020)
The study examined the risks faced by financing in Islamic banks in Sudan (a field study on a sample of Islamic banks in Sudan). The problem of the study was the lack of confirmation of the success of the projects which are financed by different Islamic financing modes due to the weakness of the funded projects. Islamic. The study aims at several objectives, including the statement of the reality of Islamic banks in the economic development in Sudan, the contribution of Islamic banks to financing projects in Sudan, seeking proposals suitable for Islamic banks to increase their effectiveness in economic development. The importance of Islamic banks is becoming necessary in the light of Islamic society. He refuses to deal with riba and works to apply Islamic law. Therefore, we find that the Islamic banks have spread clearly, and the importance of Islamic banks in the service of society and the treatment of economic problems. The study assumes several hypotheses, The study follows the historical method for tracking the previous studies related to the subject of the study, the deductive approach to determine the dimensions of the research problem, the inductive method to select the hypothesis of research, The analytical descriptive approach to the case study and the research reached several results, including the existence of legitimate control in the application of Islamic formulas when granting funding leads to reduce the risks of financing and knowledge of the provisions of credit transactions in the evil The use of Islamic formulas to reduce the risk of financing, and the use of investors to Islamic formulas reduces the risks related to financing, and recommends the following recommendations to the need to apply Islamic financing formulas in banks and financial decision makers rely on the accounting information provided by Islamic formulas and applicants to avoid funding that As it increases the risk of financing and helps to spread the severity of economic crises